Tezinsko visinski pokazatelji fudbalera ucesnika svetskog prvensta 2002 godine - Duraskovic, R.; Joksimovic, A.; Joksimovic, S. (Facta Universitatis: Series Physical Education and Sport, 2004)
Contemporary football tends more and more to demand appropriate body structure, strong, enduring bodies, extensive football intelligence, controlled aggressiveness, highly developed functional and motor abilities, and a sense for improvisation and a collective game, of football players. The aim of this research is to define the average values of all the 712 participants in the 2002 World Football Championship by analyzing height and body mass, as well as certain weight-height relations. The research results point to the fact that the average height of all the participants in the 2002 World Football Championship is 180.90 +/- 6.13 cm and the average body mass is 75.91 +/- 6.38 kg. The biggest average height was noted in the case goalkeepers, then defense and offense players, and the smallest height (178.36 +/- 5.55 cm) and body mass (73.87 +/- 5.55 kg) was noted in the case of connecting players. The first team of Brazilian football players, the champions of this tournament (2002), is distinguished from second ranked Germany and third ranked Turkey and all the other participants. Brazilian football players are on average younger, they have played longer for their national team, they are of smaller body mass and weight-height index.